Atovaquone-Proguanil combination for malaria treatment: a systematic review with meta-analysis - Oduro, Abraham , Rexford (My University, 2001)
Background: increasing spread of drug resistance among Plasmodium falciparum poses a serious threat to malaria treatment. The situation is complicated not only because new drugs are expensive and slow in development but also because they must be effective, preferably have a novel method of action, with an acceptable level of adverse effects, and be deployed in such a way as to prolong their use.
A Research Report Submitted to the School of Public Health, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the Degree of Master of Science in Medicine in Tropical Diseases (Epidemiology and Biostatistics Option). Johannesburg, January 2001
Keywords: Malaria; Atovaquone; Proguanil; Malaria, Falciparum